PENGGUNAAN MEDIA BOLA SIKNAL (BOARD GAME ALAT MUSIK TRADISIONAL) PADA PEMBELAJARAN SENI BUDAYA KELAS V - Dini, Dini Annisa Nurbaety Elsola; Insanul Qisti Bariyyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Indonesia has rich cultural resources, one of which is traditional musical instruments. This research aims to determine the application of the use of Bola Siknal’ media in class V Cultural Arts learning. This research is qualitative, with the research subjects being 8 class V students at SD Negeri Selo. The data collected in the research are the results of clipping products, observation journals, and documentation. Data collection tools include tests, research instruments in the form of observation sheets, and documentation. The results of this research show that learning using the Bola Siknal is effective in introducing traditional musical instrument material. This is evident from the results of observations during learning: all students are actively involved in group activities, and the products produced vary according to their interests, enthusiasm for learning, and students' high enthusiasm when playing Bola Siknal.